Atelectasis in obese patients undergoing laparoscopic bariatric surgery are not increased upon discharge from Post Anesthesia Care Unit - Braun, Matthias; Ruscher, Lea; Fuchs, Alexander; Kämpfer, Martina; Huber, Markus; Luedi, Markus M.; Riva, Thomas; Vogt, Andreas; Riedel, Thomas (Frontiers in Medicine, 2023)
Background: Obese patients frequently develop pulmonary atelectasis upon general anesthesia. The risk is increased during laparoscopic surgery. This prospective, observational single-center study evaluated atelectasis dynamics using Electric Impedance Tomography (EIT) in patients undergoing laparoscopic bariatric surgery. Methods: We included adult patients with ASA physical status I-IV and a BMI 40. Exclusion criteria were known severe pulmonary hypertension, home oxygen therapy, heart failure, and recent pulmonary infections. The primary outcome was the proportion of poorly ventilated lung regions (low tidal variation areas) and the global inhomogeneity (GI) index assessed by EIT before discharge from the Post Anesthesia Care Unit compared to these same measures prior to initiation of anesthesia. Results: The median [IQR] proportion of low tidal variation areas at the different analysis points were T1 10.8% [3.6%–15.1] and T5 10.3% [2.6%–18.9%]; the mean difference was -0.7% (95%-CI: -5.8%-4.5%); i.e., lower than the predefined non-inferiority margin of 5% (p=0.022). There were no changes at the four additional time points compared to T1 or postoperative pulmonary complications during the 14 days following the procedure. Conclusions: We found that obese patients undergoing laparoscopic bariatric surgery don’t leave the Post Anesthesia Care Unit with increased low tidal variation areas compared to preoperatively.